2012
DOI: 10.4236/ijmpcero.2012.13011
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of the Small Field Dosimetry Using the Acuros XB Dose Calculation Algorithm within and beyond Heterogeneous Media for 6 MV Photon Beams

Abstract: Purpose: The dosimetric accuracy of the recently released Acuros XB advanced dose calculation algorithm (Varian Medical Systems, Palo Alto, CA) is investigated for single radiation fields incident on homogeneous and heterogeneous geometries, as well as for two arc (VMAT) cases and compared against the analytical anisotropic algorithm (AAA), the collapsed cone convolution superposition algorithm (CCCS) and Monte Carlo (MC) calculations for the same geometries. Methods and Materials: Small open fields ranging fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 27 publications
1
28
0
Order By: Relevance
“…[16][17][18][19][20][21][22][23][29][30][31][32][33][34] For instance, in MC study involving low-density lung, Bush et al 17 showed the difference between the MC and AAA was higher (up to 17.5%) when compared to the one between the MC and AXB (up to 4.5%). In a phantom study involving low-density medium (lung insert and air gap), Rana et al 29 showed that the dose prediction error of the AAA could be up to 12.5% when compared to the measurements, whereas the AXB had better agreement with the measurements with a difference up to 2.8%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18][19][20][21][22][23][29][30][31][32][33][34] For instance, in MC study involving low-density lung, Bush et al 17 showed the difference between the MC and AAA was higher (up to 17.5%) when compared to the one between the MC and AXB (up to 4.5%). In a phantom study involving low-density medium (lung insert and air gap), Rana et al 29 showed that the dose prediction error of the AAA could be up to 12.5% when compared to the measurements, whereas the AXB had better agreement with the measurements with a difference up to 2.8%.…”
Section: Discussionmentioning
confidence: 99%
“…16 Detail descriptions on the AXB can be found elsewhere. [16][17] Current literature on the AXB shows that several investigators have validated the AXB by performing measurements and Monte Carlo (MC) simulations [16][17][18][19][20][21][22][23] and reported better dose prediction accuracy using the AXB than using the AAA in heterogeneous media. If the AXB is more accurate than the AAA, it is imperative to evaluate the clinical dosimetric impact of the AXB on real cancer treatment plans.…”
Section: Introductionmentioning
confidence: 99%
“…Notable was that it was one of the rare studies, where other TPS algorithm, the XVMC in this case, achieved more accurate results than the AXB algorithm, when comparing to the reference method. Stathakis et al 34 assessed the accuracy of the AXB10 with small fields (1 × 1 -5 × 5 cm 2 ) in water phantoms containing lung, bone or air inserts for 6 MV beams by comparing to full MC simulations and the AAA and the CCC algorithm implemented in Pinnacle TPS. The agreement between the AXB10 and full MC simulations was within 2% for lung and bone, but for the phantom with air, the deviations were larger -ranging from 3 to 15%.…”
Section: The Axb Algorithm and Heterogeneous Phantomsmentioning
confidence: 99%
“…The deviations in DVH parameter values between the AXB11 and the XVMC algorithm were less than 2.5%. In the study by Stathakis et al 34 jaw-collimated arc plans for lung and paraspinal lesion radiotherapy were used to benchmark the AXB10, the AAA and the CCC algorithm found in Oncentra MasterPlan against full MC simulations. With all the algorithms the deviations to full MC simulations ranged from 2% to 5%, the AXB10 being one of the algorithms with smallest discrepancies.…”
Section: The Axb Algorithm and Patient Plansmentioning
confidence: 99%
“…[18] The BEAMnrc/DOSXYZnrc code calculations were used in their study and two other analytical algorithms were assessed against MC results. The dose reduction inside lung was obtained for 1 cm × 1 cm, 2 cm × 2 cm and 3 cm × 3 cm field sizes.…”
Section: Discussionmentioning
confidence: 99%